ANALISIS FINANCIAL SHENANIGANS PADA PT TIMAH INDONESIA TBK - Malik, Abdul Qaadir; Christian, Natalis; Freanggo, Niko Nerris; Sumardi, Sumardi (Akbis: Media Riset Akuntansi dan Bisnis, 2021)
Financial shenanigans itself is all forms of action that will be carried out by the perpetrator in order to misinterpreting the truth of the company's performance itself. The purpose of this article to review the actions of financial shenanigans that conducted by PT Timah Indonesia Tbk as government ownership company. Sources of this article are based on news and the collection of previous research articles. Our finding was PT Timah Indonesia Tbk are positively manipulating their financial statement by acknowledging the existence of false income on the sale of fixed assets that is not in accordance with the revenue recognition method so that the sales report that has been published that is attached is not completely correct and gives the impression that the company's performance is in best condition.